PENGARUH PANDEMI COVID-19 TERHADAP MASYARAKAT KELURAHAN TANAH BARU KECAMATAN BEJI DALAM MELAKUKAN SWAMEDIKA - Dewi, Hasna (Politeknik Tiara Bunda, 2021)
Background: The COVID-19 pandemic has resulted in a tendency for people to prefer self-medication treatment than to undergo treatment in health facilities. Objective: To determine the effect of the COVID-19 pandemic on the attitude of the Tanah Baru Village community in carrying out self-medication and the influence of sociodemographic factors on attitudes towards self-medication during the COVID-19 pandemic. Methods: This research was conducted using a descriptive cross sectional research method. Data were collected through filling out a validated questionnaire. A total of 376 respondents who are residents of Tanah Baru village were selected by random sampling method. Data were analyzed using univariate and bivariate methods in the Statistical Product and Servicer Solution (SPSS) version 22 program. Results: Based on the results of the Chi-square test, the COVID-19 pandemic affected people's attitudes in performing self-medication significantly (p<0.05). The latest education has a significant influence on people's attitudes in carrying out self-medication before and during the COVID-19 pandemic (p<0.05). Conclusion: Based on the results of the study, it can be concluded that the COVID-19 pandemic affected the attitude of the people of Tanah Baru Medan Village in carrying out self-medication. The latest education affects people's attitudes in carrying out self-medication before and during the COVID-19 pandemic